Моделі графічних засобів захисту документів - Дурняк, Б.В.; Пашкевич, В.З. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2010)
We worked out the general model of graphic protection means of documents
which allows to provide their optimum protection according to real existing risks of their falsification.